2016
DOI: 10.1177/2058460116658686
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microlithiasis and preliminary experience of acoustic radiation force impulse imaging

Abstract: BackgroundElastography of the testis can be used as a part of multiparametric examination of the scrotum.PurposeTo determine the testicular stiffness using acoustic radiation force impulse imaging (ARFI) technique in men with testicular microlithiasis (TML).Material and MethodsIn 2013, 12 patients with diagnosed testicular microlithiasis in 2008 (mean age, 51 years; age range, 25–76 years) underwent a 5-year follow-up B-mode ultrasonography with three ARFI elastography measurements of each testis. We used a Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…Our study results were also similar to the study by D'Anastasia et al (7). Pedersen et al (14) found that the SWV range of microlithiasis areas of adults with TML to be 0.65-1.08 m/s and their study results demonstrated no significant difference between normal testes and testes with TML. In our study, the mean SWV range of testicles with TML was higher than the SWV range in the study by Pedersen et al…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study results were also similar to the study by D'Anastasia et al (7). Pedersen et al (14) found that the SWV range of microlithiasis areas of adults with TML to be 0.65-1.08 m/s and their study results demonstrated no significant difference between normal testes and testes with TML. In our study, the mean SWV range of testicles with TML was higher than the SWV range in the study by Pedersen et al…”
Section: Discussionsupporting
confidence: 92%
“…Studies in the literature have shown that none of the patients with TML developed testicular cancer after five-year follow-up in the adult group. However, there was no significant SWV difference between the patient group and the control group in a study (14). In our study, there was a statistically significant difference between the testicular SWV of the patient group and the control group.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Acoustic radiation force impulse (ARFI) is a point shear wave elastography that measures tissue elasticity independent of an external mechanical impulse to the tissue. Therefore, this method is not only useful for liver stiffness measurement but also for determination of changes in stiffness of the spleen[ 48 ], testis[ 49 ], thyroid[ 50 ], breast[ 51 ], placenta[ 52 ], pancreas in chronic pancreatitis[ 53 ] and transplanted kidney[ 54 ]. The technique is based on an acoustic impulse and measurement of the speed of the shear wave induced by it; results are displayed in m/s.…”
Section: Sonoelastrographymentioning
confidence: 99%